(3TQM Mce GHf YWGAs - (3eMeO Hf EHQGgje Hf YHGO GdfaQjs; (3eMeO haG GdTGPdj , eMeO Hf eMeO Hf eMeO GdScfOQj, CHh GdaVd (B- (3CHh GdaJM,J (B765 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfG deG QCjfG cJGH GdMce GdefShH Edi GdTjN GdEeGe Hf YWGA Gddg GdEScfOQj ef CaVd GdESfcOQj ef CaVd eG Ufa aj Ydhe GdJhMjO s
(3BNQgG (B:s
(3hfJhSd Edjg aj HdhZ gPG dCeQ hGdhUhd Edi GdSeh GdCLd hGddg GdgGOj ddUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B37 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B279s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B675s
Keywords: (3GdJUha hGdBOGH GdTQYjIs